The antecedents of social commerce service quality dimensions: a systematic review - Hanafi, Nurul Izzati; Islam, Rafikul; Maulan, Suharni (World Academy of Islamic Management, 2024)
The purpose of this paper is to provide a comprehensive review of Social Commerce Service Quality (SCSQ) and its dimensions. The authors conducted a systematic review of the extant literature on e-commerce, social commerce, service quality and e-service quality to identify the dimensions of Social Commerce Service Quality. Nine dimensions were identified, of which social interaction has been mentioned the most in the past literature, implying that it is an essential dimension for both e-service quality and social commerce platforms. Due to the virtual nature of online shopping, information quality and functional quality are the second and third most frequently mentioned dimensions for mitigating the disadvantages of online shopping. Other dimensions are privacy/security, responsiveness, design quality, reliability, personalisation, and social support. With that, this study presents an integrated model, which provides selected dimensions for researchers to further examine the SCSQ.